2017
DOI: 10.7224/1537-2073.2015-086
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Fumarate

Abstract: Background: Delayed-release dimethyl fumarate (DMF; also known as gastroresistant DMF) is indicated for the treatment of relapsing multiple sclerosis. Flushing and gastrointestinal (GI) adverse events (AEs) are common within the first few months of starting DMF therapy. Although most symptoms are mild or moderate in severity, transient, and infrequently result in treatment discontinuation, they nevertheless present a challenge for patients to adhere to therapy and achieve an optimal treatment response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The incidence of GI AEs (27%) and the proportion of patients discontinuing treatment as a result of GI AEs (5%) in our analysis was somewhat lower than has been reported in other real-world studies, but similar to what was observed in controlled clinical trials [4, 6, 11]. The data from the site survey responses indicate a high likelihood that the patients in this study were counseled about GI symptoms associated with DMF treatment.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The incidence of GI AEs (27%) and the proportion of patients discontinuing treatment as a result of GI AEs (5%) in our analysis was somewhat lower than has been reported in other real-world studies, but similar to what was observed in controlled clinical trials [4, 6, 11]. The data from the site survey responses indicate a high likelihood that the patients in this study were counseled about GI symptoms associated with DMF treatment.…”
Section: Discussionsupporting
confidence: 70%
“…Thus, it is important that counseling patients regarding potential GI AEs occurs at or before treatment initiation [4, 610]. Although most treatment-emergent GI AEs are generally mild or moderate in nature [11], these events may lead to poor treatment compliance or premature DMF discontinuation for some patients.…”
Section: Introductionmentioning
confidence: 99%
“…GI events, typically occurring within 1-2 months of treatment initiation, are among the most commonly reported AEs in clinical and real-world studies of DMF and have led to DMF treatment discontinuation in up to 20% of patients. 2,3,[11][12][13][14][15][16] In EVOLVE-MS-1, DRF appeared to be associated with lower than expected rates of GI and serious GI events based on studies with other fumaric acid esters. 1,17 In DRFtreated patients with GI AEs, events typically occurred within the first month of treatment and were short, lasting 7.5 days for most patients.…”
Section: Discussionmentioning
confidence: 89%
“…Several retrospective studies and some in real-world settings concur on the importance of counseling for DMF tolerability and GI management to enhance treatment adherence and prevent therapy discontinuation ( Begus-Nahrmann et al., 2015 , 2016 ; Min et al., 2019 ; Niemczyk et al., 2018 ; Phillips et al., 2016 ). Patients referred more to the support program after the experience of an adverse event.…”
Section: Discussionmentioning
confidence: 99%